Supervision By The Tasikmalaya Regency Bawaslu Of Campaign Violations Of Legislative Member Candidates (Dprd) In The 2024 General Elections In Tasikmalaya Regency - Sidik, Sholahudin Maulana; Solihah, Ratnia; Witianti, Siti (UNIVERSITAS PAKUAN, 2025)
In organizing general elections, the government forms election organizers, one of which is Bawaslu, whose duties and authorities include supervision of violations that often occur during elections. The challenges ahead, especially for Bawaslu Tasikmalaya Regency, are very complex, starting from human resource adaptation to technical supervision. The problems in facing these challenges include the first. In this study, the researcher wants to know, identify and analyze Bawaslu Tasikmalaya Regency's Supervision of Campaign Violations of Legislative Candidates (DPRD) in the 2024 General Election in Tasikmalaya Regency. This study uses qualitative research by describing various problems and focusing on research. The results of this study still found campaign violations in the 2024 legislative elections, violations were still found during the campaign